Huge interparietal posterior fontanel meningohydroencephalocele - Jorge Félix Companioni Rosildo; Manuel Filipe Dias dos Santos; Rita de Cassia de Santa Barbara (University of São Paulo, 2015)
Congenital encephalocele is a neural tube defect characterized by a sac-like protrusion of the brain, meninges, and other intracranial structures through the skull, which is caused by an embryonic development abnormality. The most common location is at the occipital bone, and its incidence varies according to different world regions. We report a case of an 1-month and 7-day-old male child with a huge interparietal-posterior fontanel meningohydroencephalocele, a rare occurrence. Physical examination and volumetric computed tomography were diagnostic. The encephalocele was surgically resected. Intradural and extradural approaches were performed; the bone defect was not primarily closed. Two days after surgery, the patient developed hydrocephaly requiring ventriculoperitoneal shunting. The surgical treatment of the meningohydroencephalocele of the interparietal-posterior fontanel may be accompanied by technical challenges and followed by complications due to the presence of large blood vessels under the overlying skin. In these cases, huge sacs herniate through large bone defects including meninges, brain, and blood vessels. The latter present communication with the superior sagittal sinus and ventricular system. A favorable surgical outcome generally follows an accurate strategy taking into account individual features of the lesion.